Systemic Lupus Erythematosus, Its Impact on Selected Cardiovascular Risk Factors, and Correlation with Duration of Illness: A Pilot Study - Brygida Przywara-Chowaniec; Dominika Blachut; Jan Harpula; Marcin Bereś; Agnieszka Nowak; Ewa Nowalany-Kozielska (Cardiology Research and Practice)
Systemic lupus erythematosus is a rare autoimmune disease. It leads to an increased production of proinflammatory molecules that accelerates atherogenesis and could cause an endothelium dysfunction. The aim of the study was to assess cardiovascular risk factors such as BMI and lipid profile as well as left ventricular ejection fraction among patients with SLE, and a correlation of these factors with duration of the disease. Materials and Methods. The researched group consisted of patients with SLE, being under control of the outpatient clinic of cardiology. This group included 38 patients among whom 34 were women (56.17 ± 11.05 years) and 4 were men (65.50 ± 9.22 years). The control group consisted of 19 healthy women (53.31 ± 11.94 years) and 2 healthy men (38.51 ± 7.53 years). Measurements were taken in the same conditions by trained medical staff. Results. Excessive body weight (BMI >25 kg/m2) was more frequent in the SLE group, but it was not statistically significant (55.26% vs. 52.38%, p=0.6159). LVEF values were lower in their searched group, and this factor showed statistical significance (53.92% ± 6.46 vs. 58.67% ± 4.69, p=0.0044). Thickness of the IMT was higher and statistically important among patients with SLE, both in left (1.22 ± 0.27 mm vs. 0.7 ± 0.21 mm, p=0.0001) and right common carotid artery (1.16 ± 0.26 mm vs. 0.59 ± 0.15 mm, p=0.0001), compared to the controls. Conclusions. Patients with SLE are at greater risk of developing cardiovascular diseases as the illness progresses. The activity of the disease according to the SLEDAI-2K scale may have an impact on the LVEF values which was significantly decreased in the group with active disease, but further thorough investigation is required to fully evaluate the impact of individual components of the disease and its treatment on the CVD development and mortality.